Pemberdayaan Mama Papua : Studi Kasus Pasar Cigombong Kotaraja Kota Jayapura - Sihite, Daniel Try Stovel (Program Doktor Ilmu Sosial Universitas Cenderawasih, 2022)
Seeing the importance of Empowering Mama Papua means creating conditions so that housewives can contribute their abilities to the maximum to achieve their goals. Empowerment programs that have been rolled out in Jayapura City, such as KDP, PNPM and PNPM Mandiri, Papuan Women's Cooperative, and even technical and financial assistance rolled out by several institutions tend not to touch Papuan women much. This condition, where their lives only depend on their ability to continue selling on the roadside, in between shops, traditional markets in Jayapura City. This study aims to describe how the empowerment of Papuan mothers in Cigombong Market, Jayapura City. The method used in qualitative research is emphasized on providing an actual and objective picture related to the object of research and based on data that appears in the form of words and not numbers, while the data collection method uses observation and interview techniques. Participants are Papuan women who sell at the Cigombong Kotaraja market in the city of Jayapura. In this study, it was found that the knowledge they had was generally said to be lacking because of their low educational background, namely they did not complete Junior High School (SMP) or the informal education that Papuan mothers had was very limited. And the results of the study also show that the behavior of Papuan mamas can be said to be a change in behavior, especially in terms of accepting new things that come from outside, responding in mutual cooperation and adapting to circumstances, and not feeling inferior to housewives. other. On the other hand, housewives have abandoned the habit of using time for family productive economic activities.